Donovanose - Passos, Mauro Romero Leal; Trindade Filho, José; Barreto, Nero Araújo (Brazilian Journal of Sexually Transmitted Diseases, 1996)
This article presents and extense bibliographic revision (national and intemactional literature) about donovanosis; including its histories and modem treatment.